Types of Existence in the Romance Vilnius Poker by Ričardas Gavelis - Buividavičiūtė, Lina (Respectus Philologicus, 2012)
The reception of Ričardas Gavelis’s works still remains problematic. The conception of the author’s novels is controversial, balancing between theories of modernism and postmodernism. This article focuses on one of Gavelis’s most significant novels, Vilnius poker. The analysis is based on the assumption that the postmodern structure hides the modern conception of the novel. The aims of the article are to actualize a modernpostmodern poetics and to analyze the types of existence in the romance. The possibilities of an authentic existence are analyzed in contrast to the monological, postcolonialistic “broken human being”. The analysis of the concept of authentic being is based on the philosophies of Heidegger and Kierkegaard. The concepts of dialogical and monological being are based on the works of Bakhtin and Buber. The article is based on hermeneutic methodology and the theory of dialogue. The concept of authentic being is analyzed in the context of existentialism.In the theoretical part, the author describes the problems of authentic dialogical being in general, and analyses the context of existentialism and the differences between dialogue and monologue. In the first practical part, the types of the monological being in Vilnius poker are analyzed. In the second one, the concept of authentic being in Vilnius poker is analyzed.The article draws the following conclusions: the authentic being is dialogical, polyphonic, polemic; the non-authentic being is monologicalsolypsistic-not asking, not polemic, not questioning the secrets of being, and telling only one “truth.” The monological being of the novel Vilnius poker is typical of homo lituanicus and homo sovieticus existential characters. The authentic being characterizes the protagonist Vytautas Vargalys. The dialogism of true existence is expressed by rebellious, unmasking being, the polemic with himself, the gifts of the world (inner monologue), and the others (real dialogue). The authentic being of Vytautas Vargalys is created from the senses (smell), bodies (eroticism), speaking, and musical dialogues. Unfortunately, the main character is unable to fully express his authentic being: the monological atmosphere, broken identity, and non-telling language are the main impediments to living a true dialogical life.
Keywords: existentialism; postmodernism; postcolonialism; authentic being; deconstruction; dialogism; monologism; polyphony